Case Report: Infiltrative multifocal meningioangiomatosis affecting the spinal cord of a young Labrador Retriever - Gunovska, Hana; Degl’Innocenti, Sara; Targett, Mike; Carrera, Ines; Gomes, Sergio A. (Frontiers in Veterinary Science, 2025)
Meningioangiomatosis is a rare leptomeningeal and meningovascular proliferative disorder of the central nervous system. Predilection site in dogs is the brainstem, with scarce reports of unifocal spinal meningioangiomatosis. This is the first case report of multifocal spinal meningioangiomatosis affecting the cervical, thoracic, and lumbar regions. A 2-year-old male Labrador Retriever presented for progressive ambulatory paraparesis. Vertebral column MRI revealed two presumed intramedullary space-occupying lesions, at T8–9 (large, occupying most of the spinal cord) and L3–4 (smaller, confined to grey matter); both T2-weighted hyperintense, T1-weighted isointense with contrast enhancement. Surgical exploration with durotomy revealed a unresectable well-defined mass distinct from the parenchyma of the spinal cord. Following neurological deterioration, euthanasia was performed. Multifocal to coalescing leptomeningeal and meningovascular proliferations consistent with were found on necropsy, many non-visible on MRI. This case highlights a possible differential diagnosis for multifocal spinal intramedullary masses in young dogs.